Cyclodimerization of isocyanates promoted by one large vertex metallaborane. (15th July 2018) - Ma, Pei; Spencer, James T.
Graphical abstract: The 10-vertex Manganese-decaborane [ nido -6-Mn(CO)3 B9 H13 ][NMe4 ] was found to act as an efficient catalyst for isocyanate cyclodimerization under photo-irradiation conditions. The reaction yields were comparable with other metal catalyst reported in literature. One of the products was characterized by X-ray crystallographic study and reaction mechanism was also proposed. The results are very encouraging as they represent first examples of a large metallaborane compound to catalyze the cyclodimerization of isocyanates. Abstract: The 10-vertex Manganese-decaborane [ nido -6-Mn(CO)3 B9 H13 ][NMe4 ] was found to act as an efficient catalyst for isocyanate cyclodimerization under photo-irradiation conditions. The reaction yields were comparable with other metal catalyst reported in literature. One of the products was characterized by X-ray crystallographic study and reaction mechanism was also proposed. The results are very encouraging as they represent first examples of a large metallaborane compound to catalyze the cyclodimerization of isocyanates.